The Existence of Health Literacy in Science Education: A Systematic Literature Review - Fitrah Amalia Salim; Susriyati Mahanal; Hendra Susanto (Postgraduate, University of Mataram, 2024)
Health literacy is an interesting thing to study in science learning. The purpose of this Systematic Literature Review (SLR) is to determine the trend of health literacy publications in scopus indexed journals and the potential for empowering health literacy in science learning. The keywords used were